Fallacies in the arguments for new technology: the case of proton therapy. Issue 11 (30th October 2009) - Hofmann, B
Abstract : In a seminal article in the Journal of Medical Ethics, Søren Holm and Tuja Takala analysed two protechnology arguments in bioethics: the hopeful principle and the automatic escalator . They showed how these arguments relate to problematic arguments such as the precautionary principle and the empirical slippery slope argument, and argued that they should be used with great caution. The present article investigates the recent debate on proton beam therapy, where the hopeful principle and the automatic escalator are identified. However, the debate reveals a series of other arguments that deserve similar caution. An analysis of these arguments indicates that the roots of their fallacies are to be found in the ignorance of the uncertainties about risks and benefits and an overly optimistic attitude towards technology and progress. The point is not to argue against proton therapy, but rather to point out that flawed arguments for new technologies, such as proton therapy, can actually hamper their implementation instead of promoting it. Patients deserve the best technology available, not only on the basis of the best available evidence, but also on the basis of the best arguments.